How much cropland needs to be converted to forest to offset wind erosion risk? - Y. Nykytiuk; O. Kravchenko; О. Komorna (Regulatory Mechanisms in Biosystems, 2025)
Wind erosion is one of the most underestimated forms of land degradation in European agricultural landscapes. Growing climate challenges, including more frequent and prolonged droughts as well as higher average and maximum wind speeds, significantly elevate the risk of deflation processes. However, quantitative spatial assessments of future changes in wind erosion and effective mitigation strategies remain inadequate. This study aimed to provide a detailed spatial forecast of changes in wind erosion risk due to climate change and to develop practical recommendations for optimising vegetation cover to counteract the anticipated increase in erosion potential. Modelling was conducted over a large area of Ukraine, including the Polissya, Forest-Steppe and transitional zones, using the Revised Wind Erosion Equation (RWEQ) model. The calculations incorporated detailed spatial data on climate (temperature, precipitation and wind), soil properties (grain size distribution, organic matter and calcium carbonate content) and vegetation cover and relief morphometry. Climate scenarios (SSP3-7.0, 2041–2060) were derived from WorldClim 2.1 models. Furthermore, the influence of various types of vegetation cover on reducing erosion potential was assessed. The modelling results indicate that the average annual rate of soil loss due to wind erosion is expected to increase by 1.9 times during the forecast period, while maximum values may rise by more than threefold compared to the historical period. A mosaic spatial pattern of erosion risk is emerging, characterised by pronounced risk in the northern, north-eastern and certain central regions. This risk is primarily determined by a combination of high wind speeds in winter and spring, prolonged moisture deficits (as indicated by a decrease in the potential evapotranspiration index) and low levels of calcium carbonate (CaCO 3 ) and organic matter in the soil, which diminish aggregate stability. In the southern and central regions, where soils are enriched with carbonates and organic matter, relatively high resistance to erosion processes is anticipated even in the face of unfavourable climate change. Based on ΔE calculations, which predict changes in soil loss, the necessary extent of structural adjustments to the cover was determined. Converting some arable land into forest plantations has been identified as the most effective way to mitigate the risk of wind erosion. The model indicates that the proportion of forested areas must, on average, be increased by 1.7% of the total land area to offset the rising potential for erosion. In certain erosion-prone regions, this requirement may exceed 90%. Forests provide a stable anti-erosion effect through the development of root systems, the addition of organic matter and the formation of a stable soil aggregate structure. They also offer long-term protection against wind. The results obtained are significant in that they facilitate the creation of spatially detailed risk maps and scenarios for the structural adaptation of land use. This data can be integrated into spatial planning systems, sustainable land management programmes and climate change adaptation strategies. The study also emphasises the need to develop erosion control strategies tailored to specific sites that consider the characteristics of the climate, soil and landscape structure. Prospects for further research include improving model parameterisation to take soil organic matter dynamics into account, integrating satellite monitoring to refine the spatial distribution of risks and ev a luating the synergistic effects of structural adaptations such as carbon sequestration, increased biodiversity and stabilisation of the hydrological regime.